The Ninth Grade Students’ Perception on The Use of Storytelling Skill at Mts Darul Amin Palangka Raya - Supianur Supianur; Sabarun Sabarun; Zaitun Qamariah (Badan Penerbit STIEPARI Press, 2023)
The background of this study is the influence of storytelling method to the development of students' speaking and vocabulary and students' perspectives related to the process of how they understand the storytelling material conveyed by the teacher. The objectives of the study are (1) To find out students' perceptions of the storytelling method in English class. (2) What benefits do the obtain after storytelling method applied? This study used qualitative research. Qualitative research is used in the literature as a data analysis and can also obtain results that can be adjusted based on the environment. Qualitative research can also use people as a source of research, therefore qualitative is chosen as material to assist the research being carried out by researchers. This study also used field surveys as a basic research instrument of a research that is being processed to obtain satisfactory results. The findings of this study (1) most students agree that storytelling learning is able to make students improve the quality of students' pronunciation, to be better. students view that storytelling is effective because it uses acceptable and well-implemented methods that make students feel entertained. (2) There are several ways for students to improve their pronunciation, by practicing before the lesson starts and coming to the front of the class to tell their friends. (3) Students also feel that learning storytelling is effective in adding more vocabulary, and also understand more about English.